Artisanal Italian salami and soppresse: Identification of control strategies to manage microbiological hazards. (February 2017) - Roccato, Anna; Uyttendaele, Mieke; Barrucci, Federica; Cibin, Veronica; Favretti, Michela; Cereser, Andrea; Cin, Marta Dal; Pezzuto, Alessandra; Piovesana, Alessia; Longo, Alessandra; Ramon, Elena; De Rui, Stefano; et al.
Highlights: The presence of pathogens is reported in traditional salami and soppresse. Ripening conditions for salami-soppresse vary considerably between producers. The main microbiological hazard for this type of food is Listeria monocytogenes . A weight loss of at least 25% is needed in order that products have aw ≤0.92 Products with a weight loss of 25% and without pathogens are allowed to be marketed.